IMPROVING SOLUBILITY AND DISSOLUTION OF A NATURAL PRODUCT APIGENIN VIA PREPARATION OF SOLID DISPERSION BY HOT MELT EXTRUSION - STIANI, SOFI N.; RUSDIANA, TAOFIK; SUBARNAS, ANAS (International Journal of Applied Pharmaceutics, 2021)
Objective: Hot Melt Extrusion (HME) is one of the techniques for preparing a solid dispersion hydrophilic excipient known as a no solvents practical method to increase the solubility of drugs. Apigenin (APG) has properties that thermal stable with melting point 345-350 °C but very low solubility in the water around 1,35 µg/ml. The polymer is stable in the HME method are Soluplus and Kollidon VA 64. The study aims to optimize the kind of polymer in HME formulae to improve the solubility and dissolution rate of apigenin by solid dispersion using hot-melt extrusion. Methods: Apigenin 10–50% w/w and Kollidon®VA 64 or Soluplus® and combination of Kollidon®VA 64 and Soluplus® were mixed, and the resulting blends extruded using a twin-screw extruder (Teach-Line ZK25T). Characterization of apigenin extrudates conducted using scanning electron microscopy, thermogravimetric analysis, differential scanning calorimetry, Fourier transform infrared spectroscopy, powder X-ray diffractometry, and dissolution. Results: Solubility studies presented enhancement in apigenin of 10%/Soluplus®90%; 10% w/w apigenin/Kollidon®VA 64 (90%); and 33,3% w/w apigenin/Kollidon®VA 64 33,3% mix Soluplus® 33,3% increased more than 18,25; 16,18-and 8,52-fold in water, respectively. Furthermore dissolution studies showed enhancement in apigenin percent release of 10%/Soluplus®90%; 10% w/w apigenin/Kollidon®VA 64 90%; and 33,3% w/w apigenin/Kollidon®VA 64 33,3% mix Soluplus® 33,3% tablet apigenin HME up to 34,29%; 69,75% and 30,69%, respectively. Conclusion: The formulation of 10% w/w Apigenin and 90% Soluplus® using hot-melt extrusion able to increase water solubility approximately 18,25-fold than raw material apigenin.